Employee learning motives, perceived learning opportunities and employability activities. Issue 5 (8th August 2018) - Boomaars, Chantal; Yorks, Lyle; Shetty, Rajna
Abstract : Purpose: This paper aims to examine whether employability activities are driven by employee learning motives and their perception of learning opportunities. Design/methodology/approach: Data were collected using a closed questionnaire survey from three different profit organizations ( N = 405). Hypotheses were tested through hierarchical multiple regression analysis. Findings: Hierarchical regressions showed that the learning motive "personal development" had a positive relationship with "perceived learning opportunities" and "employability activities, " as hypothesized. "Perceived learning opportunities" did not mediate the relationship between the learning motive "personal development" and "employability activities." No relationships were found among the learning motives "social pressure, " "perceived learning opportunities" and "employability activities". Originality Value: This study is among the first to investigate the motives that employees must engage in individual learning paths. It attempts to predict their self-reported employability activities based on these motives and on the learning opportunities that employees perceive.